Determination of As, Cd, and Pb in Tap Water and Bottled Water Samples by Using Optimized GFAAS System with Pd-Mg and Ni as Matrix Modifiers - Bakirdere, Sezgin; Yaroglu, Tolga; Tirik, Nihan; Demiroz, Mehmet; Fidan, A. Kemal; Maruldali, Onur; Karaca, Abdullah (Hindawi Ltd, 2013)
Arsenic, lead and cadmium were determined in tap and bottled water samples consumed in the west part of Turkey at trace levels. Graphite Furnace Atomic Absorption Spectrometry (GFAAS) was used in all detections. All of the system parameters for each element were optimized to increase sensitivity. Pd-Mg mixture was selected as the best matrix modifier for As while the highest signals were obtained for Pb and Cd in the case of Ni used as matrix modifier. Detection limits for As, Cd, and Pb were found to be 2.0, 0.036 and 0.25 ng/mL, respectively. 78 tap water and 17 different brands of bottled water samples were analyzed for their As, Cd and Pb contents under the optimized conditions. In all water samples, concentration of cadmium was found to be lower than detection limits. Lead concentration in the samples analyzed varied between N.D. and 12.66 +/- 0.68 ng/mL. The highest concentration of arsenic was determined as 11.54 +/- 2.79 ng/mL. Accuracy of the methods was verified by using a certified reference material namely Trace Element in Water, 1643e. Results found for As, Cd, and Pb in reference materials were in satisfactory agreement with the certified values.
Keywords: Atomic-Absorption-Spectrometry; Solid-Phase Extraction; Neuronal Apoptosis; Drinking-Water; Soft Drinks; Lead; Cadmium; Cancer; Preconcentration; Contamination